Implementation of green building specification credits for better thermal conditions in naturally ventilated school buildings. (April 2015) - Huang, Kuo-Tsang; Huang, Wen-Pin; Lin, Tzu-Ping; Hwang, Ruey-Lung
Abstract: Most campus buildings in public education in Taiwan are naturally ventilated. Since it is hot and humid in summer, these free-running classrooms are vulnerable to overheating, which may impair the students' learning ability. We studied a Diamond-certified green building campus to determine the effectiveness of the strategies adopted to prevent overheating by quantifying the in-room thermal comfort via long-term in situ monitoring of temperatures. The passive planning and design means used in the case are presented in detail, and the resulting synthesis effect in terms of the relation of indoor thermal comfort to student learning performance is also discussed. The maximum percentage of dissatisfaction in classrooms is 15–22% less than that in the outdoor condition, and the severity of overheating is 12.5%–18.5% of that of the outdoors. The average learning performance is around 1.3% higher than in the outdoor condition. The green building certification system (EEWH) practiced in Taiwan evaluates various aspects regarding thermal comfort enhancement, the studied naturally ventilated school building demonstrates that by complying to these EEWH credits the indoor thermal quality can successfully be ensured. Graphical abstract: Highlights: A Diamond-certified school green building was evaluated. Issues on thermal comfort and learning performance were explored. The green building certification system success in ensuring indoor thermal quality. Passive strategies for designing naturally-ventilated buildings are proposed.